Command economies, graduated responsibility, and Competence-Based Medical Education - Prost, Eric (Canadian Medical Education Journal, 2020)
Competence-Based Medical Education (CBME) rightly emphasizes that residents are adult learners who should actively take charge of their own education by ensuring they are progressing towards competence in an array of Entrustable Professional Activities (EPAs). Ironically, many CBME curricula then dictate exactly how this is to happen by listing a multitude of variables that must be checked off regarding the specifics of cases encountered. This is burdensome and unrealistic as well as contrary to the spirit of CBME. We want residents to know how to learn so they can problem solve in new situations. This is not achieved by dictating that they see nearly everything during their residency. Command economies with complete and rigid planning from above do not work. This also applies to residency training.